WITHDRAWN Co-Precipitation Synthesis of ZNCF Nanoparticle and their Structure, Morphological, and Magnetic Properties Characterization - Parajuli, D.; Vagolu, V. K.; Chandramoli, K.; Murali, N.; Samatha, K. (Journal of Nepal Physical Society, 2022)
This article was withdrawn on 7th April 2025. The withdrawal was carried out at the request of the journal’s editor and the corresponding author.